How to marry a bad boy - McKenna, Shannon (Harlequin desire, 2022)
"Step 1: Draw a random name. Step 2: Propose... Playboy Marcus Moss is the only sibling who hasn't fulfilled his grandmother's decree: marry or lose the family company. So he draws a name from all the single women working on special projects for MossTech: Eve Seaton. A brilliant, beautiful geneticist who can pretend to be his wife while he finds investors for her groundbreaking work. Win-win. Eve can't resist Marcus's promise to launch her start-up--or their sizzling attraction! But will the truth about Marcus's motives derail their arrangement?"--